Ritual Treatment of Fortunate and Unfortunate Dead by the Chinese Redemptive Society Déjiāo in Thailand - Bernard Formoso (Religions, 2020)
This paper compares the ritual management of fortunate and unfortunate dead (hungry ghosts) by a Chinese new religious movement named Déjiāo 徳教 (lit. Teaching of Virtue), which emerged in Chaozhou (the northeast of Guangdong province) in 1939, before spreading to Southeast Asia after World War II. Based on ethnographic data collected in Chaozhou and Thailand between 1993 and 2005, the analysis reveals significant differences concerning both the ideological and performative aspects of the ritual processing of the two categories of dead. The funeral care of orphaned dead by Déjiāo conforms to the Chaozhou tradition of xiū gūgú 修孤骨, a festival of second burial allegedly devised during the Song dynasty by a local Buddhist monk; most of his sequences require the activity of mediums. Turned toward the salvation of the unfortunate dead, this festival was enriched by a universalist ambition through its adaptation to the Thai context. In doing so, it perfectly expresses the moral and religious goals of Déjiāo, one of the most active Chinese redemptive societies.